INTERAKSI MASYARAKAT MULTIRELIGIUS DI DESA TEGALSARI BELITANG II OKU TIMUR SUMATERA SELATAN - Sri Astuti (Religi: Jurnal Studi Agama-agama, 2017)
This paper describes the interaction of community in building of multireligious peace. Diverse tribes and traditions that each group has trusted provide a good example in social harmony. Although they are from a various community groups, they able to build harmony. This multi society increases mutual understanding in which mutual respect for differences arise. This builds a good traditions for peoples to exchange opinions. So, harmony interaction do occurs in multi-religion and culture where building tolerance becomes ever more intense. I states that differences do not always cause violence or fragmentation of a group, but it seen that on the differences people can build a harmony society.